A Case of Adult Pancreatoblastoma With Novel APC Mutation and Genetic Heterogeneity - Suemitsu, Yamato; Ono, Yusuke; Mizukami, Yusuke; Ye, Juanjuan; Yamakawa, Keiko; Takamoto, Takeshi; Nakano-Narusawa, Yuko; Mukai, Yuri; Takamatsu, Manabu; Nakazawa, Atsuko; Mino-Kenudson, Mari; Kumasaka, Toshio; et al. (Frontiers in Oncology, 2021)
Background: Pancreatoblastoma is a rare malignant epithelial neoplasm of the pancreas that mainly occurs in children and involves abnormalities in the WNT/β-catenin pathway, such as CTNNB1 mutation. However, the molecular abnormalities in adult pancreatoblastoma are not well known. Case Presentation: An elderly man, who underwent elective distal pancreatectomy and splenectomy, was referred to our hospital with a mass in the tail of the pancreas. Histologically, the lesion revealed proliferation of clear, basophilic, and cartilaginous tumor cells with lymphatic metastasis. Each of the morphologically distinct tumor components showed different immunohistochemical patterns, indicating heterogeneous differentiation, including epithelial (both acinar and ductal), mesenchymal, and neuroendocrine differentiation. All tumor components showed nuclear expression of β-catenin and cyclin D1. Per next-generation sequencing (NGS), the clear and basophilic tumor cells shared mutations in APC, GRM8, LAMP1, and AKA9. Among the mutations, APC, c.1816_1817insA showed the highest frequency in both cell types, indicating that APC mutation was a driver mutation of the tumor. A diagnosis of PB was rendered. Summary: In conclusion, the clear and basophilic cells of the tumor were supposedly derived from the same clone and subsequently acquired additional mutations. This is the first report of clonal evolution in pancreatoblastoma.